OCCURRENCE AND SOURCES OF PENTACYCLIC TRITERPENOL METHYL ETHERS AND ALKANONES AS MOLECULAR INDICATORS IN SUSPENDED PARTICULATE MATTER FROM GREAT KWA RIVER, SOUTHEAST NIGERIA - Joe, Nna Prince; Dumka, Nwineewii Jack (Acta Scientiae et Intellectus, 2024)
Occurrence and source identification of Pentacyclic Triterpenol methyl ethers and alkanones as molecular indicators in suspended particulate matter obtained during high and low tides from Great kwa River, South East, Nigeria were characterized using gas chromatography- mass spectrometry (GC-MS) technique. Pentacyclic Triterpenol methyl ethers (PTMEs), taraxer-12-en-3-one, taraxer-14-en- 3-one, taraxerone, taraxerol, miliacin, β-amyrin methyl ether, α-amyrin methyl ether, β-amyrenyl acetate, α-amyrenyl acetate and friedelin were characterized in the suspended particulate matter. Alkanones such as 6,10, 14-trimethyl pentadecan-2- one, pentacosan-2-one, heptacosan-2-one, octacosan-2-one, nonacosan-2-one, triacontan-2-one, hentriacosan-2-one, dotriacotan-2-one and tritriacotan-2-one were also found. These distinct compounds are useful for assessing diagenetic transformation that occurs during transportation of organic detritus. PTMEs are biomarkers of specific higher plants species, while alkanones are indication of direct microbial oxidation of the n-alkanes derived from epicuticular vascular plant wax. The presence of taraxerol and its ketonic counterpart taraxerone in the sample was an indication of dominant inputs from the study area vegetation and also reflect the oxidation and direct biological inputs. The accumulation of these compounds during low tide than high tide was due to sedimentation and oxidative process of the organic matter.